Destination Conscience: Seeking Meaning and Purpose in the Travel Experience - Harald Pechlaner; Natalie Olbrich; Giulia Isetti (Emerald Publishing, 2024)
The ebook edition of this title is Open Access and freely available to read online. In a fast paced and increasingly digital world, a higher degree of sensitivity, humaneness and care in dealing with each other and in addressing feelings of isolation, alienation and fear is necessary. Within this context, the realm of tourism stands as no exception. This edited collection defines the new concept of Destination Conscience within the domain of tourism. It sheds light on the growing need for authenticity, meaning and a ""human path"" on the visitors' side, and the ability to develop such sensitivity on the destinations' side in creating meaning and responsibility. Whether through spirituality, religion, nature, history, or the subtleties of daily life, this novel paradigm fosters destinations' capacities to create meaning-driven experiences for their guests. In addition to outlining and defining the new concept of destination conscience, the inter-disciplinary approach and selected case studies and illustrative examples make Destination Conscience attractive to a variety of readers including researchers, practitioners, and postgraduate students in the fields of tourism management, spiritual and religious tourism, social sustainability, human and urban geography.
Keywords: 330; Urban Geography; Sustainability; Responsible Tourism; Religious/Spiritual Tourism; Experiences; Meaning; Ethics